TNFα Signaling Is Increased in Progressing Oral Potentially Malignant Disorders and Regulates Malignant Transformation in an Oral Carcinogenesis Model - Chadwick, Jeffrey W.; Macdonald, Rachel; Ali, Aiman A.; Glogauer, Michael; Magalhaes, Marco A. (Frontiers in Oncology, 2021)
Oral carcinogenesis represents a multi-stage process that encompasses a number of genetic and molecular changes that promote the progression of oral potentially malignant disorders (OPMD) to oral squamous cell carcinomas (OSCC). A better understanding of critical pathways governing the progression of OMPDs to OSCCs is critical to improve oncologic outcomes in the future. Previous studies have identified an important role of TNFa and TNFR1 in the invasiveness of oral cancer cell lines. Here, we investigate the expression of TNFa and TNFR1 in human OPMDs that progressed to OSCC compared to non-progressing OPMDs utilizing fluorescent immunohistochemistry (FIHC) to show increased TNFa/TNFR1 expression in progressing OPMDs. In order to interrogate the TNFa/TNFR1 signalling pathway, we utilized a 4NQO mouse model of oral carcinogenesis to demonstrate that TNFa/TNFR1 expression is upregulated in 4NQO-induced OSCC. TNFa neutralization decreased serum cytokines, inhibited the development of invasive lesions and reduced tumor-associated neutrophils in vivo. Combined, this data supports the role of the TNFa in oral malignant transformation, suggesting that critical immunoregulatory events occur downstream of TNFR1 leading to malignant transformation. Our results advance the understanding of the mechanisms governing OSCC invasion and may serve as a basis for alternative diagnostic and therapeutic approaches to OPMDs and OSCC management.